2011
DOI: 10.1007/s11186-011-9152-6
|View full text |Cite
|
Sign up to set email alerts
|

Clientelism and conceptual stretching: differentiating among concepts and among analytical levels

Abstract: The concept of clientelism has lost descriptive power. It has become indistinguishable from neighboring concepts and is applied across analytical levels. Using Gerring's (Polity 31:357-393, 1999) characterization of a "good" concept, I establish the core attributes of clientelism, which, in addition to being an interestmaximizing exchange, involves longevity, diffuseness, face-to-face contact, and inequality. Using secondary sources and fieldwork data, I differentiate clientelism from concepts such as vote-buy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 42 publications
0
36
0
18
Order By: Relevance
“…O clientelismo é uma relação de troca e, por isso, ele é mais bem definido e analisado no nível das interações entre indivíduos em vez de no nível organizacional ou no sistêmico (Hilgers 2011 troca ser mutuamente benéfica, a ausência de mecanismo crível de comprometimento faz com que a estratégia dominante para ambos os atores seja não cooperar, isto é, renegar sua promessa. Como, então, a relação clientelista se sustenta?…”
Section: Ii1 Microfundamentos Do Clientelismounclassified
“…O clientelismo é uma relação de troca e, por isso, ele é mais bem definido e analisado no nível das interações entre indivíduos em vez de no nível organizacional ou no sistêmico (Hilgers 2011 troca ser mutuamente benéfica, a ausência de mecanismo crível de comprometimento faz com que a estratégia dominante para ambos os atores seja não cooperar, isto é, renegar sua promessa. Como, então, a relação clientelista se sustenta?…”
Section: Ii1 Microfundamentos Do Clientelismounclassified
“…As far as I can see, concentrating on the micro-diversity of corrupt practices still is the preferred approach for sociologists, anthropologists and political scientists dealing with that issue (e.g. Johnston 2005;Ledeneva 2008;Hilgers 2011;Philp 2006). It would go beyond the scope of this paper to present those studies in detail and a general overview can be found in Granovetter (2007) or in Rothstein and Torsello (2013).…”
Section: And He Continuesmentioning
confidence: 99%
“…As a result, the concept of clientelism became "one of those social science concepts almost unmatched when it comes to ambiguous usage" (Gordin, 2002, p. 516), with entire articles devoted to its conceptual stretching (Hilgers, 2011).…”
Section: What Is Patronage?mentioning
confidence: 99%